A study on the degree of knowledge and evaluation of the Italian law regarding the prevention of AIDS - Cattorini, P.; Bertoli, E.; Buzzi, F.; Gornati, R.; Lazzarin, A.; Morelli, D.; Spagnolo, A. G.; Zanchetti, M. (Medicina e Morale, 1994)
The article illustrates the results of 451 questionnaires given to patients with Human Immunodcficiency Virus (HIV) hospitalized in infectious disease wards especially equipped to treat patients with AIDS or who attend the specific outpatients departments or day hospitals. In particular the study intended to check, among thc people interviewed, their real knowledge, understanding, evaluation and application of articles 5 and 6 of the Italian law n. 35 of 1990 on the "Program of urgent interventions for the prevention and fight against AIDS". These articles concern the regulations on the verification of the infection (art. 5) and the fact that employers are not allowed to carry out investigations to find out whether their employees are sieropositive (art. 6). The study was carried out in three hospitals: S. Luigi Center of the S. Raffaele Hospital of Milan (150 questionnaires), S. Matteo Polyclinic of Pavia (150 questionnaires) and the "A. Gemelli" University Polyclinic of Rome (150 questionnaires). The questionnaire was based on double questions: one on what the patient personally thinks his "rights" are and the other on what the patient thinks the law provides. In generai it seems that the subjects interviewed are aware of being "infected" people, but in a community that tends to discriminate them. Moreover they do not seem to expect the state to completely protect them even though they are willing to collaborate to change the situation and are in any case, prepared to accept legai intervention regarding themselves on condition that there is no discrimination and that their sacrifice is really useful in preventing the spreading of the disease. Finally, there appears the need to keep the state of the disease secret at work.